Developing trend and key technical analysis of intelligent acupuncture robot - Tiancheng XU; Xuejun WANG; Dongdong LU; Mengye LU; Qi LIN; Xiaoqiang ZHANG; Yi CHENG (智能科学与技术学报, 2019)
Acupuncture therapy has been adopted in more than 183 countries and regions around the world.With the rapid development of robot technology,research and development of intelligent acupuncture robot become possible,based on its core technology related research,that the point of automatic positioning and intelligent distribution point is the key technology and difficulty in research and development of intelligent acupuncture robot was pointed out in this paper,and thus,the concept of communion robot potential application value to the development of medical robot was also discussed.The latest research results of intelligent acupoint matching were also provided.